Mitogenome of the Golden Eagle (Aquila chrysaetos) in northwestern Baja California, Mexico: phylogenetic relationships and genetic variation - Francisco J. García-De León; Gorgonio Ruiz-Campos; Jesús Roberto Oyervides-Figueroa; Gonzalo De León-Girón; Carlos Alberto Flores-López; Dante Magdaleno-Moncayo; Alicia Abadía-Cardoso (Revista Mexicana de Biodiversidad)
We assembled and annotated the mitochondrial genome of golden eagles from the northwest of Baja California, Mexico, using reference and de novo strategies to analyze the synteny of mitochondrial genes, the phylogenetic relationships, and genetic variation of mitochondrial DNA. The length of the Golden Eagle mitogenome was 17,472 bp (base pairs) with a base composition of A (29.8%), C (32.5%), G (14.0%), and T (23.6%). The mitogenome contains 13 genes coding for the protein complexes coxI II-III, Cytb, cATP 6 and 8, and Nicotinamide Adenine Dinucleotide (NADH 1-6); this arrangement is consistent with the general model of the mitogenome reported in other congeneric members. Mitogenomes of individuals from northwestern Baja California are unique and they differ from the mitogenome of southern California golden eagles in 3 traits: 1) molecule size is 140 bp larger than that previously reported, 2) the addition in the annotation of a region called pseudo control (ψRC), and 3) the annotation in 2 fractions of the coding region for the protein NADH dehydrogenase subunit 3 (ND3). The genetic diversity and phylogenetic analyses of the individual genes and mitogenome support a close genetic relatedness between the golden eagles from northwestern Baja California and southern California region.